Pengaruh Penggunaan Teknologi Pembelajaran Dan Gaya Mengajar Terhadap Minat Belajar Siswa Sma Al Azhar Tanjung Bumi Bangkalan - Muhammad Yusuf; Didit Darmawan2 (Hikamatzu | Journal of Multidisciplinary, 2024)
Education in the contemporary era is increasingly influenced by technological advances and the important role of teaching style in stimulating students' interest in learning. This research aims to determine the influence of the use of learning technology and teaching styles on students' interest in learning at SMA Al Azhar Tanjung Bumi Bangkalan. The research population was 205 students at Al Azhar Tanjung Bumi Bangkalan High School, with a research sample consisting of 75 class XI students. Research includes quantitative research. Statistical analysis uses regression techniques. The results of this research reveal that there is a significant influence between the use of learning technology and teaching style on students' interest in learning at Al Azhar High School Tanjung Bumi Bangkalan. These findings provide an in-depth picture of the factors that influence students' interest in learning in the educational context at Al Azhar Tanjung Bumi Bangkalan High School, providing a basis for developing learning strategies that are more effective and in line with students' needs in this modern era